Revisão dos avanços normativos e aspectos regulatórios sobre hidrogênio verde, combustíveis sintéticos e captura de carbono no Brasil - Costa Lima, Maria Cecilia; Norberto Araújo, Danielly; Cerqueira Medrado, Ricardo; Bastos Resende, Vinicius (Latin American Journal of Energy Research, 2024)
Synthetic fuels have gained prominence as a promising alternative for the global energy transition. However, high production costs, the need for technical advancements to improve efficiency, along with the lack of supportive government policies, incentives, and regulatory frameworks, delay the implementation of these fuels. In Brazil, regulatory advances such as the Green Hydrogen Legal Framework are beginning to emerge, paving the way for the country to develop public policies that promote synthetic fuel technologies and foster diversification of the energy matrix. Thus, this article presents an analysis of regulatory and policy advances related to the development and implementation of sustainable technologies in Brazil, focusing on three areas: green hydrogen, synthetic fuels, and carbon capture. Government initiatives, state policies, financial incentives, research support, standardization and certification of green hydrogen, regulations and incentives for synthetic fuels, as well as regulatory aspects of carbon capture were analyzed. Since these are relatively new topics in Brazil, the article addresses ongoing initiatives to enable the development of these technologies in the country. Additionally, examples of regulations and policies adopted in other countries are presented.
Keywords: standards; regulations; green hydrogen; synthetic fuels; carbon capture